Phenotypic variation of a new synthetic allotetraploid Arabidopsis kamchatica enhanced in natural environment - Shimizu-Inatsugi, Rie; Morishima, Aki; Mourato, Beatriz; Shimizu, Kentaro K.; Sato, Yasuhiro (Frontiers in Plant Science, 2023)
The phenotypic variation of vegetative organ and reproductive organ of newly synthesized and natural Arabidopsis kamchatica genotypes was investigated in both controlled environment and in natural environment in an experimental garden. When we compared the variation of their leaf shape as a vegetative organ, the synthetic A. kamchatica individuals grown in the garden showed larger variation compared to the individuals incubated in a growth chamber, suggesting enhanced phenotypic variation in natural fluctuating environment. In contrast, the natural A. kamchatica genotypes did not show significant change of variation by growth condition. The phenotypic variation of floral organs by growth condition was much smaller in both synthetic and natural A. kamchatica genotypes, and the difference in variation width between the growth chamber and the garden were not significant in each genotype as well as among genotypes. The higher phenotypic variation in synthetic leaf may imply flexible transcriptomic regulation of a newly synthesized polyploid compared to a natural polyploid.